Review of the all-you-can-eat restaurant concept based on Islamic business ethics to assist the development of the national halal ecosystem: Kajian konsep restoran all-you-can-eat berdasarkan etika bisnis Islam guna mendukung pembangunan ekosistem halal nasional - Muhammad, Zaydan; Maghfuroh, Nuril Laila; Qanita, Ariza (Universitas Airlangga, 2024)
All you can eat is a restaurant or restaurant service that has a menu sales system based on only one payment for all available menus with a buffet or buffet concept with a certain time limit. In Indonesia, many restaurants or places to eat have provided all you can eat because of the pretext of attracting customers and increasing turnover. However, there are still many places to eat that provide non-halal menus that are contrary to Indonesia's vision as a global halal center in 2024. In this study, a qualitative descriptive method was used with literature and Islamic business ethics as a supporting study. The purpose of this study is to conceptually describe all you can it in accordance with Islamic business ethics and support the creation of a halal ecosystem in Indonesia. So that it can produce research output that can be used as a reference later for restaurants or restaurants that provide an all you can it menu that is in accordance with the principles of Islamic business ethics and still maintains halal status.